Ferry Supriyanto, Imelda, Sri Gustini, PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MUSI BANYUASIN - Fery Supriyanto; . Imelda; Sri Gustini (Jurnal Manajemen Kompeten, 2018)
This research entitled "The effect of work motivation towards job performance of Badan Penanggulangan Bencana Daerah employees of Musi Banyuasin Regency". Population in this research is 60 persons of Badan Penanggulangan Bencana Daerah employees of Musi Banyuasin regency. The sample of this research is all of BPBD employees Musi Banyuasin regency, so that this reaserch is called as population research, where all of population with the total number of 60 is as sample. Sampling technique that is used is using saturated sampling. The research findings showed that Motivation has impact towardsemployees' job performance of Badan Penanggulangan Bencana Daerah Musi Banyuasin regency. from the validity and reliability testresult by using SPSS is got if r obtained value≥ r table, motivation value is 0.610 and employees' job performance value is 0.616 so this value is higher than r critical value of product moment that is 0.254 (look at appendices of r table).Constants is 6.218, regression coeffisient of motivation variable (X) is 0.851. Based on t-test value ia got that t-obtained value is higher than t - table value (14.569 > 2.002).